Kekerabatan Bahasa Jawa Serang dengan Bahasa Jawa Surabaya (Kajian Leksikostatistik) - Nadofah Nadofah; Lia Andriani; Khusnul Yuliyanti; Asep Muhyidin (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
A language certainly has a relationship with other languages, even though they are related, there will definitely be differences in vocabulary, grammar, and so on. The aim of this research is to determine the percentage of kinship and separation time between Serang Javanese and Surabaya Javanese from their parent languages. This research was conducted using qualitative and quantitative descriptive methods with lexicostatistical methods. The data source comes from informants who are native speakers of Serang Javanese and Surabaya Javanese using 200 Swadesh vocabulary. Collecting data using basic listening techniques, skillful listening, recording and note-taking techniques. The results show that Serang Javanese and Surabaya Javanese are at the same language level as seen from the percentage obtained, namely 83%, so both are included in dialects. This kinship can be seen from the similarity of 130 identical vocabularies and 36 sound correspondences. These two languages separated 347—428 or around 1,676 to 1,595 years ago starting from the time this research was conducted, namely in 2023.